Comparative analysis of treatment outcomes in osteoarthritis knee: integrating physiotherapy and medication versus mono-therapies - B., Raghav; S. M., Arvind Kumar; Sandhiya; Mathew, Anil C. (International Journal of Research in Orthopaedics, 2024)
Background: Osteoarthritis (OA) of the knee is a prevalent degenerative joint disorder that significantly impacts patients’ mobility and quality of life. Effective management of knee OA is crucial to alleviate symptoms and improve daily functioning. This study aims to conduct a comparative analysis of treatment outcomes for knee OA by evaluating three distinct therapeutic approaches: a combination of physiotherapy and medication, physiotherapy alone and medication alone, all supplemented with routine daily activities. Methods: The research involves a cohort of patients diagnosed with knee OA, divided into three groups, each receiving one of the specified treatments. Outcome measures include pain reduction, assessed through the Visual Analog Scale (VAS); functional mobility, evaluated using the Timed Up and Go (TUG) test; and overall quality of life, measured by the Knee Injury and Osteoarthritis Outcome Score (KOOS). Results: Preliminary findings suggest that patients receiving the integrated treatment of physiotherapy and medication show significantly greater improvements in pain relief and functional mobility compared to those undergoing mono-therapies. The combination approach appears to leverage the synergistic effects of both modalities, offering a more comprehensive management strategy. Physiotherapy alone also demonstrates notable benefits in enhancing mobility and reducing pain, while medication primarily provides symptomatic relief. Conclusions: This study underscores the importance of a multidisciplinary approach in treating knee OA, highlighting that integrated treatment plans may offer superior outcomes. These findings aim to inform clinical practice, suggesting that combining physiotherapy with medication can optimize therapeutic efficacy, improve patient quality of life and potentially alter the standard care protocols for knee OA. Further research is warranted to substantiate these results and explore long-term benefits.